2022
DOI: 10.1177/09504222221091989
|View full text |Cite
|
Sign up to set email alerts
|

Work placement learning and student employability: Do student satisfaction, commitment and achievement matter?

Abstract: While the extant literature generally suggests a positive relationship between work placement learning (WPL) and student employability, the mechanisms underlying this relationship remain unclear and under-researched. Against this background, this study draws on insights from experiential learning and self-determination theories to explore the mediating effects of student satisfaction, commitment and achievement on the relationship between WPL and student employability. The study adopted a quantitative approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Previous studies (Chukwuedo and Ementa, 2022; Okolie et al, 2021a; Okorie et al, 2022; Otache and Edokpolor, 2022) have found a positive and significant link between WPL and perceived employability, and employability preparatory behaviours. These findings are relevant given that, through WPL, higher education institutions (HEIs) can partner with industry to offer students opportunities to gain a practical understanding of work-related theoretical knowledge they may have gained in the classroom (e.g.…”
mentioning
confidence: 74%
“…Previous studies (Chukwuedo and Ementa, 2022; Okolie et al, 2021a; Okorie et al, 2022; Otache and Edokpolor, 2022) have found a positive and significant link between WPL and perceived employability, and employability preparatory behaviours. These findings are relevant given that, through WPL, higher education institutions (HEIs) can partner with industry to offer students opportunities to gain a practical understanding of work-related theoretical knowledge they may have gained in the classroom (e.g.…”
mentioning
confidence: 74%
“…Model 4 of the PROCESS Macro was used to test the mediating effect of ATVB, and Model 1b was used to test the moderating effect of educational level because the moderator variable is categorical. The hypothesised relationships were considered significant if the confidence interval excluded zero (Otache et al , 2022; Otache and Edopkolor, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…However, there is an acknowledgement of the interplay between personal and structural factors of self-perceived employability (Vanhercke et al, 2014), captured via person, context, and time dimensions of a sustainable career (De Vos et al, 2020). One approach to enhancing students' self-perceived employability is a year-in-industry placement (herewith referred to as a placement) (Otache and Edopkolor, 2022). The placement forms part of a sandwich degree, whereby a traditional 3-year undergraduate course is supplemented by an additional placement year before the final year of study.…”
Section: Setting the Scenementioning
confidence: 99%